Penyusunan Sitasi dan Daftar Pustaka Otomatis Menggunakan Mendeley bagi Mahasiswa - Sakir, Ahmad Rosandi; Nurwijaya, Sugian; Almahdali, Humairah (Lok Seva: Journal of Contemporary Community Service, 2024)
The training on using the Mendeley application for Public Administration students at the Faculty of Social and Political Sciences, Universitas Pattimura, aims to enhance skills in managing references and citations systematically. The main issue faced by students is the difficulty in organizing references structurally and the risk of citation errors that can affect academic quality. This activity includes preparation, material delivery, and hands-on practice using the Mendeley application. The training is based on the Theory of Technology Acceptance Model (TAM), which explains how technology adoption can influence its effectiveness. The results show that students can manage references more systematically and gain confidence in writing academic papers, including final assignments. Moreover, the training positively contributes to improving the overall academic quality on campus. Beyond teaching the technical aspects of using the application, this training also raises students' awareness of the importance of academic ethics in reference management. Thus, this training serves as a strategic step to prepare students for academic challenges while promoting a stronger culture of scientific writing.